2015
DOI: 10.4269/ajtmh.14-0631
|View full text |Cite
|
Sign up to set email alerts
|

Age Modifies the Immunologic Response and Clinical Presentation of American Tegumentary Leishmaniasis

Abstract: Abstract. Leishmania (Viannia) braziliensis is the main causal agent of American tegumentary leishmaniasis (ATL) that may present as cutaneous, mucosal, or disseminated cutaneous leishmaniasis. The disease is highly prevalent in young males and there is a lack of studies of ATL in the elderly. Herein, we compared clinical manifestations, immunologic response, and response to antimony therapy between patients 60 years of age (N = 58) and patients who were 21-30 years of age (N = 187). The study was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…9,11 One possible explanation for these discordant findings could be the differences in the illness duration between the two groups, which was longer in the elderly than in young patients in previous studies. 9,11 Here, because the inclusion criteria limited the illness duration to between 30 and 60 days and because one of the matching criteria for control selection was a similar time of lesion duration, we did not detect any difference in ulcer size between the two groups. We confirmed the observation that there is a lower frequency and smaller size of satellite lymph nodes in elderly than young subjects.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…9,11 One possible explanation for these discordant findings could be the differences in the illness duration between the two groups, which was longer in the elderly than in young patients in previous studies. 9,11 Here, because the inclusion criteria limited the illness duration to between 30 and 60 days and because one of the matching criteria for control selection was a similar time of lesion duration, we did not detect any difference in ulcer size between the two groups. We confirmed the observation that there is a lower frequency and smaller size of satellite lymph nodes in elderly than young subjects.…”
Section: Discussionmentioning
confidence: 90%
“…We have previously shown that PBMCs from elderly patients with CL produce less antigen-induced IFN-γ and more IL-10 than PBMCs from young patients. 11 Here, we extended the characterization of the immune response by measuring IL-1β, CXCL9, and TNF levels in the two groups of patients. No significant difference was observed between the groups regarding the production of these cytokines (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we did not find an increase in children or women with mucosal disease, over the study period, there was an increase in the proportion of patients age 60 years and older. We know that infected sandflies can be documented inside of houses and in peridomiciliary areas, 24 which might increase the risk of exposure among children, women, and older adults who are more likely to spend time in these areas compared with young adult men who tend to do daytime agricultural work. The lack of an increase in the number of ML cases in children and women, however, makes it unlikely that the observed trend in older adults is related to a change in the transmission pattern.…”
Section: Discussionmentioning
confidence: 99%